Dermatopathia pigmentosa reticularis - Gauri Vats; Rohit Kataria; Durgesh Sonare; Vinod Jain (Wolters Kluwer Medknow Publications, 2018)
Dermatopathia pigmentosa reticularis (DPR) is a rare disorder with characteristic triad of generalized reticulate hyperpigmentation, noncicatricial alopecia, and onychodystrophy. A 12-year-old Indian boy presented with classical features of the triad along with adermatoglyphia, hyperhidrosis, punctate hyperkeratosis of palm, and sole along with keratosis pilaris. Histopathology suggested a diagnosis of DPR with a differential of Naegeli-Franceschetti-Jadassohn syndrome and dyskeratosis congenita.